Lighting up lives through cooking gas and transforming society - Barua, S. K. (SAGE business cases., 2020)
Cases of the Indian Institute of Management Ahmedabad are prepared as a basis for class discussion. Cases are not designed to present illustrations of either correct or incorrect handling of administrative problems.